Assessment of the factors contributing to the variations in microcystins biodegradability of the biofilms on a practical biological treatment facility. (January 2015) - Li, Jieming; Shimizu, Kazuya; Akasako, Haruna; Lu, Zhijiang; Akiyama, Shohei; Goto, Masafumi; Utsumi, Motoo; Sugiura, Norio
Highlights: Dynamics in microcystin-biodegradability depend on microcystin-degrader biomass. Degrader abundance relates to water temperature, microcystin and chlorophyll-a amount. The peaks of degrader biomass and biodegradation follow peaks of some abiotic factors. No difference exists in separate and concurrent biodegradation of microcystin analogs. Microcystin-degraders proliferate to varied extents along biodegradation processes. Abstract: This study revealed the biotic and abiotic parameters driving the variations in microcystins (MCs) biodegradability of a practical biological treatment facility (BTF). Results showed that similar trends of seasonal variation were seen for microcystin-LR (MCLR) biodegradability of biofilms on the BTF and indigenous MCLR-degrader population, where both peaks co-occurred in October, following the peaks of natural MCLR concentration and water temperature observed in August. The lag period might be required for accumulation of MCLR-degraders and MCLR-degrading enzyme activity. The MCLR-degrader population was correlated to temperature, MCLR and chlorophyll-a concentration in water where the biofilms submerged, indicating that these abiotic and biotic parameters exerted direct and/or indirect influences on seasonal variation in MCLR-biodegradability. In comparison, no effect of other co-existing MCs on biodegradation of one MC was observed. However, proliferation of MC-degraders along biodegradation processes positively responded to total amount of MCs, suggesting that multiple MCs contributed additively to MC-degrader proliferation.